Kinetic analyses of intramolecular dehydration of hexitols in high-temperature water. (January 2020) - Yamaguchi, Aritomo; Mimura, Naoki; Shirai, Masayuki; Sato, Osamu
Abstract: Intramolecular dehydration of the biomass-derived hexitols D-sorbitol, D-mannitol, and galactitol was investigated. These reactions were performed in high-temperature water at 523–573 K without added acid catalyst. The rate constants for the dehydration steps in the reaction networks were determined at various reaction temperatures, and the activation energies and pre-exponential factors were calculated from Arrhenius plots. The yield of each product was estimated as a function of reaction time and temperature using the calculated rate constants and activation energies. The maximum yield of each product from the dehydration reactions was predicted over a range of reaction time and temperature, allowing the selective production of these important platform chemicals. Graphical abstract: Image 1 Highlights: The intramolecular dehydration of biomass-derived hexitols was performed. The rate constants for the dehydration steps in the reaction networks were determined. The yield of each product was estimated as a function of reaction time and temperature. Products can be selected by choosing the appropriate reaction time and temperature.